Prevalência de dor multirregional e associação com a capacidade para o trabalho – estudo transversal - Vieira, Ludmilla Maria Souza Mattos de Araújo (Universidade Federal de São Carlos, 2020)
Introduction: Multisite pain (MSP) has been studied among the working population because it is associated with reduced work ability. In Brazil, studies have investigated pain without addressing MSP and its interference with work ability. Objective: To evaluate the prevalence of MSP among Brazilian workers from different occupations and to associate MSP with the work ability. Methods: Data from the BRAzilian eValuation of Occupational health (BRAVO) database were analyzed. In the primary surveys, workers aged between 18 and 70 years and with a work routine of at least 20 hours per week were included. BRAVO database contain information about personal data, musculoskeletal symptoms (Nordic Musculoskeletal Questionnaire), job content (Job Content Questionnaire) and work ability (Work Ability Index). All studies were approved by the Ethics Committee and all participants gave written informed consent. Data were analyzed using logistic and linear regression. Sex, age, comorbidities (hypertension, mild emotional disorder and gastritis), type of work (blue-collar, white-collar) and job content were included as covariates in the regression models. Results: The prevalence of MSP was 58% (95% CI=53-62%) among Brazilian workers, being 57% (95% CI=52-62%) among white-collar workers and 53% (95% CI=40-66%) among blue-collar workers. There was a significant association between MSP and reduced work ability. The presence of MSP increases the chance of low work ability between 1.7 and 5.3 times. A dose-response relationship was also found, as increasing one pain site causes a reduction of 0.9 to 1.2 points in the work ability. Conclusions: MSP is highly prevalent among Brazilian workers and should be addressed due to its impact on reducing work ability.
Prevalence of multisite pain and association with work ability - cross-sectional study
Keywords: Saúde ocupacional; Ergonomia; Fisioterapia; Occupational health; Ergonomics; Physical therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL